PENGARUH PENGANGGARAN PARTISIPATIF TERHADAP SENJANGAN ANGGARAN DENGAN KEPERCAYAAN MANAJERIAL SEBAGAI VARIABEL INTERVENING - Tresnanty, Astrid; Widanaputra, A. A. G. P (E-Jurnal Akuntansi, 2015)
This research was conducted in order to know the effect of participatory budgeting on budgetary slack with managerial trusts as an intervening variabl e . The sample in this study are 160 officials in faculties and departments at Udayana University who participated in the preparation of the budget and meet the criteria for purposive sampling. The data analysis technique used in this study is path analysis. The results of the analysis concluded that participatory budgeting directly affects budgetary slack. Variable managerial trusts also affect the relationship of budget participation on budgetary slack become an indirect relationship.
Keywords: participatory budgeting, budgetary slack, managerial trusts